Functional and Phenotypic Characterization of B Cells in the Teleost Adipose Tissue - Simón, Rocío; Martín-Martín, Alba; Morel, Esther; Díaz-Rosales, Patricia; Tafalla, Carolina (Frontiers in Immunology, 2022)
The immune response of the adipose tissue (AT) has been neglected in most animal models until investigations in human and mice linked obesity to chronic inflammation, highlighting the immune nature of this tissue. Despite this, in teleost fish, only a few studies have addressed the immune role of the AT. These studies have mostly focused on reporting transcriptional changes in the AT in response to diverse intraperitoneally delivered stimuli. Although the presence of B cells within the AT was also previously revealed, these cells have never been phenotypically or functionally characterized and this is what we have addressed in the current study. Initially, the B cell populations present in the rainbow trout (Oncorhynchus mykiss) AT were characterized in comparison to B cells from other sources. As occurs in other rainbow trout tissues, IgM+IgD+, IgM+IgD- and IgD+IgM- B cell subsets were identified in the AT. Interestingly, AT IgM+IgD- B cells showed a transcriptional profile that agrees with that of cells that have committed to plasmablasts/ plasma cells, being this profile much more pronounced towards a differentiation state than that of blood IgM+IgD- B cells. Accordingly, the IgM-secreting capacity of AT B cells is significantly higher than that of blood B cells. Additionally, AT IgM+IgD+ B cells also showed specific phenotypic traits when compared to their counterparts in other tissues. Finally, we established how these B cell subsets responded when rainbow trout were intraperitoneally injected with a model antigen. Our results demonstrate that the AT hosts plasmablasts/ plasma cells that secrete specific IgMs, as happens in the peritoneal cavity and systemic immune tissues. Although the presence of these antigen-specific IgM-secreting cells was more abundant in the peritoneal cavity, these specific differentiated B cells were detected in the AT for long time periods at levels similar to those of spleen and head kidney. Our results provide new evidence regarding the immune role of the teleost AT, indicating that it functions as a secondary lymphoid organ that promotes immunity to peritoneal antigens.